Molluscan diversity of Jhapa District, Eastern Nepal - Subba, Bharat Raj; Pandey, Manish Raj (Journal of Natural History Museum, 2008)
A detailed study made on the collection of molluscs from 33 different study sites of Jhapa District revealed the presence of 17 species of freshwater and 4 species of land mollusc. Key words: Mollusc; land; freshwater; Jhapa J. Nat. Hist. Mus. Vol.22, 2005 p.22-27